Characterization of Myxococcus xanthus MazF and Implications for a New Point of Regulation - Boynton, Tye O. (2013)
During development, Myxococcus xanthus cells undergo programmed cell death (PCD) whereby 80% of vegetative cells die. Previously, the MazF RNA interferase has been implicated in this role. Recently, it was shown that deletion of the mazF gene does not eliminate PCD in wild-type strain DK1622 as originally seen in DZF1. To clarify the role of MazF, recombinant enzyme was characterized using a highly sensitive assay in the presence and absence of the proposed antitoxin MrpC. In contrast to previous reports that MrpC inhibits MazF activity, the hydrolysis rate was enhanced in a concentration-dependent manner with MrpC or MrpC2, an N-terminally truncated form of MrpC. Furthermore, MazF transcripts were not detected until 6–8 hours post-induction, suggesting an antitoxin is unnecessary earlier. Potential MazF targets were identified and their transcript levels were shown to decline in DK1622 while remaining steady in a mazF deletion strain. Elimination of the mazF hydrolysis site in the nla6 transcript resulted in overproduction of the mRNA. Thus, MazF negatively regulates specific transcripts. Additionally, we show that discrepancies in the developmental phenotypes caused by removal of mazF in DK1622 and DZF1 are due to the presence of the pilQ1 allele in the latter strain.